IMPLEMENTASI STRATEGI PENGENDALIAN PERILAKU SEDENTARI DALAM MENEKAN BEBAN OSTEOARTRITIS LUTUT DAN PENGUATAN SISTEM PELAYANAN KESEHATAN: STUDI KASUS-KONTROL DI RSU MUHAMMADIYAH METRO - W. Azhar Na'im; Muhammad Faris Nuuruddin; Nabila Nur Afifah Fitri (Journal of Hospital Administration and Excellent Health Service, 2026)
Knee osteoarthritis is one of the main causes of chronic pain, disability, and reduced quality of life in adult and elderly populations. Sedentary behavior, like spending a lot of time sitting due to changes in work patterns and technology use, is thought to increase the burden of this musculoskeletal disease. This study aimed to analyze the relationship between sedentary behavior and the occurrence of knee osteoarthritis, as well as to outline strategic policy implications for the healthcare system. The study used a case-control design at RSU Muhammadiyah Metro. The results showed that sedentary behavior has a very strong connection with the occurrence of knee osteoarthritis. Individuals with sedentary behavior are 23.276 times more likely to develop knee osteoarthritis compared to those who are not sedentary (OR = 23.276; p < 0.001). Based on the strength of this association, committing to promoting physical activity, integrating early screening into primary healthcare services, and strengthening community-based prevention programs are high-value healthcare investment choices to maintain the sustainability of National Health Insurance (JKN) funding. Keywords: knee osteoarthritis, sedentary behavior, healthcare services, case-control, JKN.